Pengaruh Tipe Industri, Kepemilikan Saham Pemerintah, Profitabilitas Terhadap Sustainability Report - Adiatma, K. Baba; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 25 No 2 (2018), 2018)
Companies that move business regardless of social and environmental responsibility cause damage to the company's environment and social. Sustainability report is a control tool for sustainability risk that can provide economic, corporate and social information. Companies that publish sustainability reports are still small, indicating that there are factors affecting sustainability reports. The purpose of this study to determine whether the type of industry, government stock ownership, profitability affect sustainability report. The population of this study are all companies listed on the BEI in 2013-2016. Sampling using purposive sampling method. The sample consists of 12 companies observed for four years so that the number of samples is 48. The research data is obtained from the annual report of each company. The suitable method for analyzing this research is multiple linear regression. From the analysis, it is found that industry type has a positive effect on sustainability report, while government ownership and profitability have no effect on sustainability report. Keywords : industry type, government share ownership, profitability, sustainability report.